2016
DOI: 10.1590/s0100-204x2016000900026
|View full text |Cite
|
Sign up to set email alerts
|

Cor do solo na identificação de áreas com diferentes potenciais produtivos e qualidade de café

Abstract: Resumo -O objetivo deste trabalho foi verificar a eficácia da cor do solo na identificação de áreas com diferentes potenciais produtivos e qualidade de café, em Argissolo Vermelho-Amarelo desenvolvido de arenito, no Planalto Ocidental Paulista, no Estado de São Paulo. Coletaram-se 173 amostras em 39 ha, para a determinação de matiz, valor, croma e índice de avermelhamento do solo, com base nos dados da espectroscopia de reflectância difusa (ERD). Avaliaram-se, também, a produtividade e a qualidade do fruto de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
1
3
0
1
Order By: Relevance
“…Silt presented the lowest value of range, showing a higher spatial variability. TPV presented a range slightly higher than 150 m and the other attributes showed ranges higher than 200 m. In addition, TS was the most homogeneous attribute, demonstrated by a range value close to 300 m. Similar results were observed in areas with similar geology and pedology (Sanchez et al, 2005;Carmo et al, 2016;Siqueira et al, 2010b), which reinforce the relationship between soil physical quality and the geology of the area.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Silt presented the lowest value of range, showing a higher spatial variability. TPV presented a range slightly higher than 150 m and the other attributes showed ranges higher than 200 m. In addition, TS was the most homogeneous attribute, demonstrated by a range value close to 300 m. Similar results were observed in areas with similar geology and pedology (Sanchez et al, 2005;Carmo et al, 2016;Siqueira et al, 2010b), which reinforce the relationship between soil physical quality and the geology of the area.…”
Section: Resultssupporting
confidence: 75%
“…Santos et al (2017) studied the physical attributes of a sandy textured Oxisol cultivated with conilon coffee and found a lower coefficient of variation for macropores (27.60%), total sand (8.72%), silt (18.43%), and clay (18.30%) when compared to the results obtained in our study, being the result of differences in the soil type found in the area. Carmo et al (2016), studying the quality of the beverage coffee as a function of soil color and attributes of an Ultisol (Argissolo Vermelho Amarelo, Brazilian Soil Classification System) from sandstone in the State of São Paulo, verified coefficients of variation for clay that ranged from 17 to 24%. On the other hand, Sanchez et al (2005) studied the soil physical attributes of an Oxisol (Latossolo Vermelho-Amarelo, Brazilian Soil Classification System) cultivated with coffee in the State of Minas Gerais and observed, on average, coefficients of variation of 10% for clay content.…”
Section: Resultsmentioning
confidence: 99%
“…Although determining colors in the field and in the laboratory involves different steps, the color obtained by DRS can be useful in various study conditions. Carmo et al (2016), for example, assessed DRSestimated colors to distinguish areas regarding the yield and quality of coffee (Coffea arabica L.) bean, and Peluco et al (2015) showed that the DOR, measured by DRS, can assist in mapping and identifying areas with different potential of phosphorus adsorption. It should be noted that Hm and Gt, two mineral pigment agents of soils (Lepsch, 2011), have different phosphorus adsorption capacities in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Diffuse reflectance spectroscopy (DRS) and magnetic susceptibility (MS) are alternative techniques that can be used to estimate soil properties such as: iron oxides (Viscarra Rossel et al, 2010;Bahia et al, 2015); silicate minerals, including kaolinite, illite, and smectite (Viscarra Rossel, 2011;Mulder et al, 2013); chemical attributes and grain size Demattê et al, 2016;Viscarra Rossel et al, 2016); phosphorus adsorption (Camargo et al, 2015;Peluco et al, 2015); and soil color (Aquino et al, 2016;Carmo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A cor do solo é apontada, por muitos pedólogos, como uma das propriedades morfológicas mais significativas, que, por meio dela, é possível verificar informações a seu respeito. Os principais fatores que influenciam na tonalidade que o solo irá apresentar está atrelada, principalmente, ao material de origem (rochas), posição na paisagem, vegetação, clima, umidade, presença de matéria orgânica e mineralógica (Carmo et al, 2016).…”
Section: Determinação Da Cor Do Solounclassified